2020
DOI: 10.1111/hae.13949
|View full text |Cite
|
Sign up to set email alerts
|

Activity measurements of dalcinonacog alfa

Abstract: Introduction Many recombinant and modified FIX products have been, and continue to be, developed with the aim of improving treatment for patients with haemophilia B. One such new product is dalcinonacog alfa, a recombinant FIX with modifications to provide improved features such as subcutaneous administration. Aim In view of previously observed assay discrepancies with modified FIX therapeutics, the aim of this study was to assess potential discrepancies in potency measurement of dalcinonacog alfa between and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Although this study initially used a chromogenic activity assay, we subsequently learned that the activity of dalcinonacog alfa is best determined by a onestage assay. 25,26 Last, only patients aged 12 to 65 years were enrolled in this study. 27,28 These data demonstrated that DalcA may be efficacious for the treatment of hemophilia B (with the ab-…”
Section: Discussionmentioning
confidence: 99%
“…Although this study initially used a chromogenic activity assay, we subsequently learned that the activity of dalcinonacog alfa is best determined by a onestage assay. 25,26 Last, only patients aged 12 to 65 years were enrolled in this study. 27,28 These data demonstrated that DalcA may be efficacious for the treatment of hemophilia B (with the ab-…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies are required to monitor immunogenicity to dalcinonacog alfa. Although this study initially utilized a chromogenic activity assay, we subsequently learned that the activity of dalcinonacog alfa is best determined by a one-stage assay [ 44 , 53 ] Results presented in Fig 3D thus represent those of the one-stage clotting assay. Interestingly, a significant correction in the WBCT and aPTT was observed within the first 24 hours after the first dose of 300 IU/kg dalcinonacog alfa, whereas the observable plasma levels of FIX activity were approximately 5% and negligible antigen was detected.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of rFIX antigen in canine plasma samples was determined using an ELISA (Asserachrom IX:Ag, Diagnostica Stago, cat no 00943). Baseline antigen levels were undetectable [ 44 ]. FIX activity was assessed at Haematologic Technologies using an activated partial thromboplastin time (aPTT) Factor IX one-stage clotting assay on an ACL-TOP instrument (Instrumentation Laboratories) using the recommended HemosIL ® or SynthasIL ® reagents and calibrators.…”
Section: Methodsmentioning
confidence: 99%
“…Dalcinonacog alfa activity measurement variability between platforms and reagents has been published, including data that the chromogenic assay should not be used. 15 FIX activity was assayed at Haemtech Biopharma Services (Essex Junction, Vermont, USA), with an activated partial thromboplastin time (aPTT) FIX one‐stage clotting assay on an ACL‐TOP instrument (Instrumentation Laboratory) applying the recommended SynthASil ® (Instrumentation Laboratory) reagents and calibrators. Clearance, volume of distribution at steady‐state and half‐life (t 1/2 ) (alpha and beta phase) were determined from day 28 and subsequent samples during washout.…”
Section: Methodsmentioning
confidence: 99%
“…Dalcinonacog alfa activity measurement variability between platforms and reagents has been published, including data that the chromogenic assay should not be used. 15 (Siemens Enzygnost TAT kit) were performed at the central laboratory. Anti-drug antibodies (ADA) to dalcinonacog alfa and BeneFIX were detected through a direct binding enzyme-linked immunosorbent assay (ELISA).…”
Section: Assessmentsmentioning
confidence: 99%